2019
DOI: 10.1111/jce.14203
|View full text |Cite
|
Sign up to set email alerts
|

Part II—Clinical presentation, electrophysiologic characteristics, and when and how to ablate atriofascicular pathways and long and short decrementally conducting accessory pathways

Abstract: Recognition of the presence, location, and properties of unusual accessory pathways for atrioventricular conduction is an exciting, frequently difficult, challenge for the clinical cardiac arrhythmologist. In this second part of our series of reviews relative to this topic, we discuss the steps required to achieve the correct diagnosis and appropriate management in patients with the so‐called “Mahaim” variants of pre‐excitation. We indicate that, nowadays, it is recognized that these abnormal rhythms are manif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 35 publications
3
15
0
Order By: Relevance
“…Atrial component of decremental accessory pathways, found in the vestibule of the tricuspid valve, could harbor remnants of the tissues that give rise to the normal AV node (4). Localization of the area of recording of a specific potential in our case was consistant with the location of the vestibule of the tricuspid valve (4) and thus could appear to be a 3D representation of what has been described in autopsies (3,4). The relative wide area of recording was not indicative of common accessory pathway potentials, neither the long VA interval was evocative of conduction through an usual accessory pathway where local ventricular and atrial events are commonly fused.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Atrial component of decremental accessory pathways, found in the vestibule of the tricuspid valve, could harbor remnants of the tissues that give rise to the normal AV node (4). Localization of the area of recording of a specific potential in our case was consistant with the location of the vestibule of the tricuspid valve (4) and thus could appear to be a 3D representation of what has been described in autopsies (3,4). The relative wide area of recording was not indicative of common accessory pathway potentials, neither the long VA interval was evocative of conduction through an usual accessory pathway where local ventricular and atrial events are commonly fused.…”
Section: Discussionsupporting
confidence: 51%
“…Thus, it seems to be the first report of orthodromic reciprocating tachycardia using a purely concealed decremental accessory pathway with findings compatible with an accessory AV node. Some more common by-pass tracts however may also have decremental properties without being categorized as Mahaim fibers : these short decrementally conducting AV pathways may simply be due to alteration of conduction properties or tortuosity (4,11). However they usually do not present with retrograde conduction (2,12) and large areas of specific potentials are not described in this setting.…”
Section: Discussionmentioning
confidence: 99%
“…Adenosine also terminates APs with decremental conduction properties such as atriofascicular tachycardia and PJRT. 19…”
Section: Avrt/avnrtmentioning
confidence: 99%
“…Adenosine creates a conduction block in the slow pathway in AVNRT and in the AV node in AVRT. Adenosine also terminates APs with decremental conduction properties such as atriofascicular tachycardia and PJRT 19 …”
Section: Therapeutic Uses Of Adenosinementioning
confidence: 99%
See 1 more Smart Citation